2014
DOI: 10.1016/j.hrthm.2013.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial repolarization dispersion and autonomic nerve activity in a canine experimental acute myocardial infarction model

Abstract: Background Evidence from a canine experimental acute myocardial infarction (MI) model shows that until the seventh week after MI the relationship between stellate ganglionic nerve and vagal nerve activities (SGNA/VNA) progressively increases. Objective We evaluated how autonomic nervous system activity influences temporal myocardial repolarization dispersion at this period. Methods We analyzed autonomic nerve activity as well as QT and RR variability from recordings previously obtained in 9 dogs. From a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 45 publications
1
31
0
1
Order By: Relevance
“…24,26,27 Therefore, the mean and variance values for each of these intervals were calculated and then the original formula proposed by Berger et al34 was used to calculate three different QT variability indexes (QTVIs) (Figure 3). 24,26,27 QTnormaleVI=log10{[[QTnormalevariance]/[QTnormalemean]2][[RRvariance]/[RRmean]2]}QTnormalpVI=log10{[[QTnormalpvariance]/[QTnormalpmean]2][[RRvariance]/[RRmean]2]}normalTnormaleVI=log10{[[normalTnormalevariance]/[normalTnormalemean]2][[RRvariance]/[RRmean]2]}…”
Section: Methodsmentioning
confidence: 99%
“…24,26,27 Therefore, the mean and variance values for each of these intervals were calculated and then the original formula proposed by Berger et al34 was used to calculate three different QT variability indexes (QTVIs) (Figure 3). 24,26,27 QTnormaleVI=log10{[[QTnormalevariance]/[QTnormalemean]2][[RRvariance]/[RRmean]2]}QTnormalpVI=log10{[[QTnormalpvariance]/[QTnormalpmean]2][[RRvariance]/[RRmean]2]}normalTnormaleVI=log10{[[normalTnormalevariance]/[normalTnormalemean]2][[RRvariance]/[RRmean]2]}…”
Section: Methodsmentioning
confidence: 99%
“…Piccirillo et al [27] showed, in a canine experimental acute myocardial infarction model, that, during congestive heart failure, the reduction of LF power and LF/HF ratio probably reflect diminished sinus node responsiveness to autonomic modulation or an abnormal baroreflex function. In another study of the same authors, they showed that LF and HF power were significantly lower seven weeks after acute canine myocardial infarction than at baseline [29]. Other authors have proposed that LF is predominantly associated with parasympathetic activity based on the findings: increases in HF and LF occur after the use of drugs that specifically enhance the cardiac vagal tone; there is similarity of LF values between individuals with cardiac sympathetic denervation and normal baroreflex sensitivity; some validated measures of sympathetic control of the heart, such as plasma epinephrine levels and cardiac norepinephrine spillover, are not correlated with LF [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…a) Sim1: The model in (12), represented in Fig. 1B, was utilized to simulate the case where TF coherence between output y(t) and input x(t), γ ref 2 xy (t) = a(t), changes quickly over time, therefore modulating the proportion of the output power related and unrelated to input x(t), denoted as P y,rx (t) and P y,ux (t), respectively.…”
Section: Materials a Simulation Studymentioning
confidence: 99%
“…Figure 3 shows the results of Sim1, which demonstrate that the method for correcting for the TF coherence bias provides accurate estimates. Mean trends of γ TOT xy (t), P TOT y,rx (t) and P TOT y,ux (t), calculated from mean TF representations obtained from 100 realizations of the model in (12), are shown along with their corresponding theoretical values. Before correcting for the bias (panels on the left), estimated trends correlated well with the theoretical patterns (correlation coefficients > 0.96), but the relative estimation error was high, being equal to 24% ± 25% for γ TOT xy (t), 103% ± 94% for P TOT y,rx (t) and −36%±10% for P TOT y,ux (t) (mean ± standard deviation).…”
Section: A Coherence Bias Correctionmentioning
confidence: 99%